1978
DOI: 10.2307/3897622
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Forage Consumption by Cattle in Arizona Ponderosa Pine Forests

Abstract: Highlight: Forage consumption was significantly correlated with forage production and tree density, but not with steepness of slope, rockiness of soil, or distance from water. This suggests that good range management practices can effectively distribute livestock use. Management practices designed to increase multiple use values of ponderosa pine forests are being tested in Arizona (Brown et al. 1974). Some of these practices will increase herbage production (Clary 1975), but there is a question as to what ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1982
1982
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 3 publications
1
6
0
Order By: Relevance
“…This difference in use was reflected both by amount of vegetation consumed per ha (Table 2) and by number of animals observed in the type. Similar results were found by Clary et al (1978) in Northern Arizona. The Dougas fir-elk sedge type received more use near water, but use rapidly decreased with distance away from water.…”
Section: Vegetation Types and Forage Usesupporting
confidence: 87%
“…This difference in use was reflected both by amount of vegetation consumed per ha (Table 2) and by number of animals observed in the type. Similar results were found by Clary et al (1978) in Northern Arizona. The Dougas fir-elk sedge type received more use near water, but use rapidly decreased with distance away from water.…”
Section: Vegetation Types and Forage Usesupporting
confidence: 87%
“…Studies on cattle distribution and behavior have taken place in such places as Arizona (Clary et al 1978), Utah (Cook 1966), Oklahoma (Dwyer 1962), and Oregon (Roath and Krueger 1982). No comparable research has been conducted in conifer/ tall shrub ecosystems such as are commonly found in northern Idaho.…”
mentioning
confidence: 99%
“…Climate, soils, floristic composition, grazing management, and animal husbandry practices are all known to affect cattle mobility (Clary et al, 1978;Stuth, 1991;Bailey et al, 2008;Rubio et al, 2008) and thus potentially could have contributed to the treatment difference. However, as noted in the Methods section, considerable care and effort was applied when pairing Impact and Control study areas with the intent of controlling these potentially confounding factors.…”
Section: Impact Versus Controlmentioning
confidence: 99%